The Determinants of Student Test Scores: Academic, Family, and Learning Environment Factors a Multiple Linear Regression Analysis - Rena Nainggolan; Fenina Adline Twince Tobing (IJNMT (International Journal of New Media Technology), 2026)
This study aims to analyze the influence of academic, family, and learning environment factors on student exam scores. The study employs a quantitative approach using secondary data in the form of the Student Performance Factors dateset comprising 6,607 observations. The dependent variable in this study is student exam scores (Exam_Score) [1], while the independent variables include study hours (Hours_Studied), attendance (Attendance), previous scores (Previous_Scores), tutoring sessions (Tutoring_Sessions), parental involvement (Parental_Involvement), and access to learning resources (Access_to_Resources) . The analytical techniques used were descriptive statistics and multiple linear regression. The results indicate that the regression model is statistically significant simultaneously with an F-value of 1,601 and p < 0.001, and explains 66.0% of the variation in students’ exam scores (R² = 0.660). Partially, study hours, attendance, previous scores, and tutoring sessions have a positive and significant effect on test scores. Additionally, students with higher levels of parental involvement and access to learning resources tend to achieve better test scores [2] . These findings indicate that students’ academic achievement is not solely determined by individual study effort but is also influenced by family support and the availability of an adequate learning environment.